Effects of inter and intraspecific diversity and genetic divergence of aquatic fungal communities on leaf litter decomposition-a microcosm experiment - Andrade, Ricardo (2016)
Freshwater fungi play a key role in plant litter decomposition and have been used to investigate the relationships between biodiversity and ecosystem functioning in streams. Although there is evidence of positive effects of biodiversity on ecosystem processes, particularly on biomass produced, some studies have shown that neutral or negative effects may occur. We manipulated the composition and the number of species and genotypes in aquatic fungal assemblages creating different levels of genetic divergence to assess effects of fungal diversity on biomass produced and leaf decomposition. Generally, diversity effects on fungal biomass produced were positive, suggesting complementarity between species, but in assemblages with more species positive diversity effects were reduced. Genotype diversity and genetic divergence had net positive effects on leaf mass loss, but in assemblages with higher diversity leaf decomposition decreased. Our results highlight the importance of considering multiple biodiversity measures when investigating the relationship between biodiversity and ecosystem functioning.